Spondylo-mesomelic-acrodysplasia with joint dislocations and severe combined immunodeficiency: a newly recognised immuno-osseous dysplasia. Issue 10 (October 1997) - Castriota-Scanderbeg, A; Mingarelli, R; Caramia, G; Osimani, P; Lachman, R S; Rimoin, D L; Wilcox, W R; Dallapiccola, B
Abstract : A newborn girl is described with an association of spondylo-acrodysplasia, mild short limbed dwarfism without significant metaphyseal changes, joint dislocations, and severe immune system dysfunction. This association is distinct from other known immuno-osseous dysplasias, including Schimke dysplasia, ADA deficiency with osseous changes, and Omenn phenotype with short limbed dwarfism.